Does digitalization lead to climate awareness? A cross-country panel data analysis - Md. Bokhtiar Hasan; Md. Tapan Mahmud; Mohammed Gazi Salah Uddin; Ali M. Ahmed; Donghyun Park; John Beirne (Asian Development Bank (ADB), 2025)
Climate change, currently one of the most pressing challenges, requires increased public awareness and decisive action to support effective mitigation efforts. Comprehending digitalization's potential role in shaping public understanding of climate-related issues has become a progressively important area of study. Against this backdrop, we undertake a pioneering attempt to examine how digitalization influences climate change awareness across diverse countries. To capture the multifaceted nature of digitalization, we construct a digitalization index, applying principal component analysis. Leveraging an annual panel dataset encompassing 65 countries over 2005-2020, our study applies several econometric techniques: panel-corrected standard errors, feasible generalized least squares, two-step system generalized method of moments, and panel quantile regression, to investigate this nexus. Our findings unveil a nonlinear U-shaped relationship between digitalization and climate awareness, suggesting that digitalization initially has a negligible or adverse impact but substantially boosts climate awareness after a digital maturity threshold is achieved. Furthermore, the share of renewable energy consumption also follows a U-shaped nonlinear pattern, while household consumption and corruption control contribute to boosting climate awareness. Conversely, the impact of human development, gross fixed capital, and trade openness becomes negligible when endogeneity is controlled. Our quantile-based analysis further validates these conclusions, although some factors vary across quantiles. These findings carry important policy implications, particularly emphasizing targeted fiscal policies to strengthen digital infrastructure and climate communication efforts, thereby facilitating tailored strategies for improved public climate awareness to meet climate sustainability.
Keywords: C33; O11; Q01; Q54; 330; digitalization; climate awareness; panel data analysis; nonlinear relationship